Treatment approaches for alcohol and drug dependence : an introductory guide - Jarvis, Tracey J.; Wiley InterScience (Online service) (Hoboken, NJ : John Wiley, 2005)
The first edition of this book was based upon the recommendations of the Quality Assurance in the Treatment of Drug Dependence Project, and provided a step-by-step-guide for therapists working with clients with alcohol or other drug dependency or misuse.
Treatment Approaches for Alcohol and Drug Dependence; Contents; About the Authors; Practice Sheets and Client Handouts; Foreword by Nick Heather; How to Read this Book; Acknowledgements; PART I LAYING THE FOUNDATIONS; PART II STRATEGIES FOR ACTION; PART III MAINTAINING CHANGE; PART IV SPECIAL GROUPS AND MANAGEMENT ISSUES; PART V DESIGNING AN INTERVENTION; Index.
Previous ed. cataloged under: Jarvis, Tracey J.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Substance abuse -- Treatment; Substance-Related Disorders -- therapy; Psychotherapy -- methods; Polytoxicomanie -- Traitement; Electronic books